Investigation of the influence of oxygen on the rate and anisotropy of deep etching of silicon in the plasma-chemical reactor with the controlled magnetic field - B. B. Гладковський; O. A. Федорович (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The article presents the research results on the influence of the amount of oxygen in a mixture with sulfur hexafluoride on the rate and anisotropy of the silicon etching in the plasma-chemical reactor with the controlled magnetic field. The etching was performed under the pressure of (0,3—2,0)·10–3 Torr in the working chamber and the energy of chemically active ions of 50—80 eV. It was possible to etch the silicon to the depth of 100 µm with anisotropy 10, using a thick (0.4—1 µm) nickel mask. The obtained results make it evident, that maximums do not coincide for speed of etch and anisotropy. The maximum of etch rate is observed at oxygen maintained at 5%. While the maximum of anisotropy is observed at 10% oxygen. The authors discovered the influence of the magnetic field on the rate and anisotropy of etching. Etch rate of the silicon at the increase of the magnetic-field tension increases virtually twofold at other discharge parameters remaining unchanged. The anisotropy first increases, and then decreases sharply. Thus, the increase of the tension of magnetic field results in worsening of anisotropy. Thus, the process of deep plasma-chemical etching of silicon has been developed and optimized.